The effects of carbon content on the microstructure and elevated temperature tensile strength of a nickel-base superalloy - Wei, Chao-Nan; Bor, Hui-Yun; Chang, Li (My University, 2010)
This study investigates how carbon content affects the microstructure and elevated temperature tensile strength of fine-grain CM-681LC superalloy. Experimental results indicate that increasing the carbon content from 0.11 to 0.15 wt% increases the total area fraction of carbides considerably. However, the two alloys exhibit similar carbide shapes and sizes, probably because the short solidification time in the fine-grain process limits the growth of carbides. Besides, carbon addition significantly reduces the area fraction of gamma-gamma' eutectic phases from 8.6 to 5.3% because the eutectic phase forming elements are consumed by (Ta, Hf)C carbides and the carbides occupy the position of gamma-gamma' eutectic phases during the solidification. Further, the carbon addition improves the mechanical strength by about 6% and the elongation by about 50% in tensile tests at 760 degrees C and yields favorable tensile performance at elevated temperature. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Carbon; Grain refinement; Nickel-base superalloy; Hot isostatic pressing; Microstructure; Tensile test